Mesenchymal chondrosarcoma of mandible: A rare case report and review - Singh, Priyanka (Medknow Publications & Media Pvt Ltd, 2014)
Mesenchymal Chondrosarcomas (MCs) are rare malignant connective tissue neoplasms representing approximately 1% of all chondrosarcomas (CSs) that can arise from both soft and hard tissues. They are distinct tumors arising in unicentric or multicentric locations. The tumor is most unusual as it has been described as a particularly aggressive neoplasm with a high tendency for late recurrence and delayed metastasis. It is a biphasic tumor with areas comprising of spindle cell mesenchyme having areas of chondroid differentiation. Here we report a case of 60-year-old male with mesenchymal CS of the mandible.